Upaya Meningkatkan Hasil Belajar Ips Peserta Didik Melalui Penerapan Metode Kerja Kelompok Kelas VII pada SMP PGRI Tumbang Mirah Kecamatan Katingan Tengah - Sutria Ningsih; Muhammad Jailani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This study aims: (1) Increasing the activity of IPS VII grade students in SMP Tumbang Mirah, (2) Knowing the learning outcomes of Social Sciences class VII of PGRI Tumbang Mirah Middle School. The method used by researchers is to use the Classroom Action Research (CAR) design. For data collection techniques used were observation and tests with a population of 30 IPS VII grade students of PGRI Tumbang Mirah Middle School. The data analysis technique used is qualitative data analysis and quantitative data analysis. The results showed that: (1) the learning activities of IPS 7th grade students of SMP Tumbang Mirah using more active Group Work Method Implementation, (2) there was an increase in Accounting learning outcomes of IPS VII grade students of SMP Tumbang Mirah using Application of Group Work Methods which shows Accounting learning outcomes in the first cycle obtained an average of 68.5% with 66.6% classical completeness and in the second cycle an average of 7.8% with 93.3% classical completeness.